Anomalies of Mullerian ducts - Padhye, Saraswati M (Journal of Kathmandu Medical College, 2014)
Some form of mullerian anomalies occur in one out of 4000 to 5000 females. A girl presenting with primary amenorrhoea, pelvic pain and sub fertility is likely to have some or other form of mullerian anomalies. Here, we present seven cases of mullerian anomalies who were treated at Kathmandu Medical college Teaching hospital in seven years. Absence of vagina usually is not obvious in a female baby at the time of birth. It is only when the secondary sex characters develop; time of menarche is awaited but one does not menstruate that the parents start wondering why her menstruation did not start. DOI: http://dx.doi.org/10.3126/jkmc.v3i2.11232 Journal of Kathmandu Medical College Vol. 3, No. 2, Issue 8, Apr.-Jun., 2014 Page: 82-87